Respuesta :
Given the graph of y = 2x² is transformed into y = -2x² + 3.
For any function y = f(x), the transformation y' = -y = -f(x) reflects the graph across x-axis.
So it means that y = -2x² is the reflection of y = 2x² across the x-axis.
For any graph y = g(x), the transformation y' = y + k = g(x) + k shifts the graph 'k' units upward for all value of 'k' > 0.
So it means that y = -2x² + 3 is the shifted version of y = -2x² by '"3 units up".
Hence, option B and C are correct i.e. "reflection across x-axis" and "shift of 3 units up".